PENGEMBANGAN KETERAMPILAN BERBICARA PADA ANAK SEKOLAH DASAR KARENA ADANYA ERA DIGITALISASI - Rifa'a Noveyanti; Siti Rokmanah; Nana Hendracipta (STKIP Subang, 2023)
One of the eras or times in this life that has experienced a lot of progress and has given rise to digital forms is the digital era. Humans will not be able to slow down the rapid progress of the digital era. Thus, when conducting research in a natural setting with the intention of understanding the events that occur, various pre-existing approaches are applied. The developmental process, often known as maturation in English, is qualitative, systematic, and something that everyone must go through, receptive and expressive elements both play a role in language development, which is a stage of childhood development, the active language ability is speaking. Speaking is considered active because the speaker chooses the words and media to be used. The purpose of this study is to increase knowledge in the era of digitalization. According to the nurturing approach and environmental color, children have the capacity to develop a unique personality. Being able to provide the best for the child is important for parents.